“Being that can be understood is language”: A Contemplation on the Implications of Gadamer’s Thesis Concerning Language - Abdollah Amini (Journal of Philosophical Investigations, 2024)
Hans-Georg Gadamer, in his work Truth and Method, raises a controversial and thought-provoking argument regarding language and its relation to Being. He states that “Being that can be understood is language.” Despite his subsequent efforts in some works following Truth and Method to elucidate what he considers to be self-evident in the meaning of this expression, various interpreters have continued to derive various interpretations from it. Some have focused on its ontological dimension within Heideggerian context, while others have emphasized its epistemological aspect within the Kantian tradition. In this paper, we aim to clarify the meaning of the Gadamer’s expression and explore the grounds and reasons for the emergence of conflicting interpretations, while also referencing such interpretations and relying on a descriptive-analytical approach based on Gadamer’s relevant texts. Overall, it seems that the ambiguity in Gadamer’s position regarding language and its relation to being boils down to the fact that he seeks to reconcile Heidegger’s phenomenological perspective with his own philosophical hermeneutics. Thus, Gadamer sometimes emphasizes on the being itself and sometimes on our linguistic understanding of being.